Fertility incentives in Canada: A cohort analysis - Siha Lee; Sitian Liu (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
We study the fertility effects of the 1997 Quebec Family Policy, which introduced universal childcare and simultaneously ended its newborn allowance. Using a 20% sample of Canadian tax returns, we find that the reform reduced overall fertility at the intensive margin but had varying impacts by life stage. For younger cohorts of women early in their careers and family planning, the reform increased their likelihood of having a first or second child without reducing employment, suggesting that subsidized childcare may have helped young women balance work and family life. In contrast, for older cohorts of women, most of whom already had at least one child, the reform boosted employment but decreased the likelihood of having more children, implying that increased maternal employment may have raised the opportunity costs of additional children.
Keywords: J13; 330; Family policy; fertility; childcare; newborn allowance